Body image perceptions and symptoms of disturbed eating behavior among children and adolescents in Germany - Kathrin Schuck; Simone Munsch; Silvia Schneider (BMC, 2018)
Abstract Theoretical background Body image distortions such as perception biases are assumed to be precursors of eating disorders (ED). This study aims to investigate body image perceptions and symptoms of disturbed eating behavior among a sample of 11-17 year-old students in Germany. Methods A cross-sectional survey study was carried out among 1524 students of twelve secondary schools from all school types in North Rhine-Westphalia (Germany). A naturalistic photograph-rating consisting of photographs of young women's bodies was used to examine children's perceptions of female bodies (i.e., perceived average body size and perceived ideal body size of young women). Also, symptoms of disturbed eating behavior were examined. Results Compared to statistical data, children and adolescents underestimated the average body size of young women by more than two BMI-points (estimated average BMI = 20), with no differences between boys and girls. Also, girls and boys generally held a slim female thin-ideal (perceived ideal BMI = 19.5), which is nearly three BMI-points below the average body size in the young female population. Girls showed a slightly stronger female thin-ideal than boys. Among all subgroups, early-adolescent girls (13-14 years) displayed the strongest thin-ideal internalization. Nearly one-third of this group perceived a BMI below 18 as ideal female body size. Symptoms of disturbed eating behavior were common among youth and most frequent among adolescent girls (15-17 years). Girls who displayed a bias towards underestimation of female body size and girls who displayed an underweight female thin-ideal were more likely to report harmful dieting behaviors and psychological distress associated with eating, body, and weight. Conclusions This study found that 11-17 year-old girls and boys do not show accurate judgements regarding the average body size of young women. Instead, there is systematic and significant underestimation, indicating considerable perception biases, which may constitute a risk factor for the development and maintenance of ED. Symptoms of disturbed eating behavior were common, especially among girls, and associated with body-related perceptions. Future research will need to clarify the severity and course of these symptoms.